Permasalahan Kredit Perbankan Syariah: Analisis Manajemen Risiko Kredit di Bank Muamalat Manado - Cantika Aurelia Ramadina Taha; Chadijah Haris; Rosdalina Bukido (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2022)
This study describes the effectiveness of credit risk management at Bank Muamalat. The research was conducted at Bank Muamalat Manado. Researchers used qualitative research methods with a descriptive approach. The primary data was collected using semi-structured interviews with Bank Muamalat Manado, and then a three-stage analysis was carried out, data reduction, presentation, and decision-making. Researchers found effectiveness in controlling credit risk at Bank Muamalat. This can be proven by the significant decrease in 2018-2019, namely from 226 to 117 total customers with problems. In addition, researchers also found that in 2020-2021, 198 to 184 total customers with problems. There are two ways of controlling credit risk applied by Bank Mualamat. First, the selection of four criteria, namely personality, psychology, capacity, capital, collateral, and situation. Second, so there are no troubled customers, the bank takes four stages: voluntary payments, AYDA, WO, and collateral auctions. Both of these methods are very important to reduce the occurrence of non-tearing financing. However, credit risk at Bank Muamalat can arise if the evaluation of potential clients and financing strategies from financial institutions are not strict.